ITEM RESPONSE THEORY APPROACH: KALIBRASI BUTIR SOAL PENILAIAN AKHIR SEMESTER MATA PELAJARAN BAHASA ARAB - Danni, Rahmat; Wahyuni, Ajeng; Tauratiya, Tauratiya (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2021)
This study describes the item details of the final semester questions in Arabic MAN 1 Pangkalpinang using the item response theory approach. The problem behind this research is that the development of Arabic final assessment items did not go through the correct stages. Therefore, this research is quantitative research. The subjects of this study were 176 students of class XI MAN 1 Pangkalpinang. The answer data is in the form of answers to questions in the final semester in Arabic which are 40 multiple-choice items with five answers. The results showed that the final results of the Arabic semester (1) proved valid, indicated by 40 items (100%) with loading factors; (2) proven to be reliable, indicated by the reliability coefficient of 0.884; (3) there are 33 items (82.5%) of the 40 items that have a good level of difficulty and distinguishing power so that they can be stored in the question bank and used in subsequent activities, while 7 items (17.5%) are item number 10, 26, 27, 29, 32, 34, and 35 do not meet the criteria for a good level of difficulty so they need to be revised or eliminated; and (4) suitable for use in students with low to moderate ability (Î¸) in the range -3.5 to +1.5 in logit. Future research is expected to be able to analyze Arabic language question items in the form of descriptive tests on a large scale or develop high-quality high-order thinking skills in Arabic.